2018
DOI: 10.17509/ijal.v8i1.11478
|View full text |Cite
|
Sign up to set email alerts
|

Washback of English national exams at ninth-grade level in Thailand and Indonesia

Abstract: Washback refers to influences of testing on teaching and learning. In Thailand and Indonesia, washback of the Ordinary National Educational Test (O-NET) and Ujian Nasional (UN) inevitably occurs on teaching and learning in classrooms at every level. This present study aims to explore and compare the washback effects of the O-NET and UN on English language learning as perceived by Thai and Indonesian ninth-grade students. It is a multi-case study (Thailand case and Indonesia case) by using triangulation design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In these boarding schools, the students acquire the pragmatic competence of the Arabic and English languages as two international languages. Thus, based on previous observations, "the school students in Indonesia work hard to pass national exams but do not perform well in the Illocutionary force indicating device" (Sundayana et al, 2018), and students of boarding schools lack an interlanguage model for developing their pragmatic competence in those two languages, for example, in terms of the acquisition and development of the speech acts of apologizing. This issue is essential because of the fact that the students of the Islamic boarding schools are taught to perceive a high degree of politeness based on Islamic values.…”
Section: Introductionmentioning
confidence: 99%
“…In these boarding schools, the students acquire the pragmatic competence of the Arabic and English languages as two international languages. Thus, based on previous observations, "the school students in Indonesia work hard to pass national exams but do not perform well in the Illocutionary force indicating device" (Sundayana et al, 2018), and students of boarding schools lack an interlanguage model for developing their pragmatic competence in those two languages, for example, in terms of the acquisition and development of the speech acts of apologizing. This issue is essential because of the fact that the students of the Islamic boarding schools are taught to perceive a high degree of politeness based on Islamic values.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the research on washback is determined as an empirical study because it is related to the actual experiences and activities of the teachers and the students in the classroom. Washback of a test is worth studying since it inevitably occurs and affects teachers and students in a myriad of ways (Sundayana et al, 2018)…”
Section: )mentioning
confidence: 99%
“…Negative effects from high-stakes testing are not limited to Thailand. A study conducted by Sundayana, Meekaeo, Purnawarman, and Sukyadi (2018) found that schools in Thailand and Indonesia set up special test preparation programs to enhance students' test-taking skills before the actual test. Further evidence was obtained in the study of Lunrasri (2014), who determined that school principals in one province of Thailand directed teachers to conduct special classes to go over old test exams, as well as tutor and train students to cope with the actual test.…”
Section: Research Questionmentioning
confidence: 99%